The impacts of digital transformation on HR efficiency in KSA (International Journal of Financial, Administrative and Economic Sciences, 2024)
Digital transformation is one of the most significant modern mechanism concerned with restructuring the traditional labor market into digital work as a result of keeping pace with technical and technological progress. In the Kingdom of Saudi Arabia, Vision 2030 emphasized the activation and development of digital transformation in all government and private sectors, therefore, the aim of this study is to identify the impact of digital transformation on the efficiency of human resources, and determine the potential benefits of adopting digital transformation on the development of human resources. Furthermore, the study attempts to find whether there is link between the impact of demographic characteristics variables, such as (age, academic qualification, years of experience) on efficiency, identifying the concept and benefits of digital transformation. The questionnaire as a tool to suit the nature of the study, and the study population consisted of workers in Saudi banks, and it was distributed in a simple random way, and the number of responses reached (45) male and female employees, and the SPSS statistical analysis program was used to analyze the data.As one of the most important findings of the two researchers is the existence of a statistically significant positive correlation relationship between digital transformation and human resource efficiency, as the Pearson correlation coefficient reached (0.726), which is a statistically significant value at the level of significance (0.01), and there are no statistically significant differences in organizational efficiency. Referring to any of the demographic variables, the analysis showed that the level of organizational efficiency in the sample community is high by a percentage of 91.1%, in light of the findings of the study. The two researchers recommended expanding training centers on technological programs and activating them to develop human resources, and educate organizations and society about the advantages of Modern technology and its positive impact on the efficiency of employees, raising the spirit of competition and cooperation between organizations to create new digital growth that seeks to achieve the vision of 2030.
Keywords: Digital Transformation; Vision 2030; Efficiency; Human Resources